Cerium Oxide-Decorated γ-Fe2O3 Nanoparticles: Design, Synthesis and in vivo Effects on Parameters of Oxidative Stress - Moskvin, Maksym; Marková, Irena; Malínská, Hana; Miklánková, Denisa; Hüttl, Martina; Oliyarnyk, Olena; Pop-Georgievski, Ognen; Zhigunov, Alexander; Petrovský, Eduard; Horák, Daniel (Frontiers in Chemistry, 2020)
Magnetic γ-Fe2O3/CeOx nanoparticles were obtained by basic coprecipitation/oxidation of iron chlorides with hydrogen peroxide, followed by precipitation of Ce(NO3)3 with ammonia. The appearance of CeOx on the magnetic particle surface was confirmed by X-ray photoelectron spectroscopy (XPS), powder X-ray diffraction (XRD), and elemental analysis; a magnetometer was used to measure the magnetic properties of γ-Fe2O3/CeOx. The relatively high saturation magnetization of the particles (41.1 A∙m2/kg) enabled magnetic separation. The surface of γ-Fe2O3/CeOx particles was functionalized with PEG-neridronate of two different molecular weights to ensure colloidal stability and biocompatibility. The ability of the particles to affect oxidative stress in hereditary hypertriglyceridemic (HHTg) rats was tested by biological assay of the liver, kidney cortex, and brain tissues. An improvement was observed in both enzymatic (superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx)) and non-enzymatic (reduced (GSH) and oxidized (GSSG) glutathione) levels of antioxidant defense and lipid peroxidation parameters (4-hydroxynonenal (4-HNE) and malondialdehyde (MDA)). The results corresponded with chemical determination of antioxidant activity based on 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, proving that in the animal model γ-Fe2O3/CeOx@PEG2,000 nanoparticles effectively scavenged radicals due to the presence of cerium oxide, in turn decreasing oxidative stress. These particles may therefore have the potential to reduce disorders associated with oxidative stress and inflammation.